Knowledge and attitude towards birth spacing and copper T usage among women of reproductive age group - Singla, Neha; Kaur, Taranjit; Tanisha; Kaur, Tajveer; Kaur, Simrat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Birth spacing is the time interval between two births. Short birth intervals or inter-pregnancy intervals are associated with negative maternal health outcomes as well as negative perinatal, neonatal, and infant health outcomes. Safety effective methods of contraception such as copper T-380 A, have allowed many women around the world to avoid the health risks of unwanted pregnancy and have provided for the spacing of pregnancies. The objective of the present study was to assess the level of knowledge and attitude towards birth spacing and copper-T usage among women of reproductive age group and to determine the relationship between knowledge and attitude towards birth spacing and copper T usage among women. Methods: This study was conducted at a tertiary care hospital in Ludhiana from March to December 2022. The research included 150 women who met the following criteria: they were of reproductive age, married, had at least one child, and consented to participate in the study. Results: The study found that 66.7% of the women had an average level of knowledge about birth spacing, while 59.3% had an average level of knowledge regarding the use of copper T. Additionally, 82.7% of the women exhibited a positive attitude towards both births spacing and the use of copper-T. Conclusions: Despite the majority of women demonstrating good knowledge and a positive attitude towards birth spacing and copper T usage, most were not utilizing any birth spacing methods at the time of data collection. To address this gap, it is crucial to enhance awareness about birth spacing and encourage the adoption of at least one method. This can help prevent unplanned, untimely, and high-risk pregnancies.